MIXED MODEL ASSEMBLY LINE BALANCING FOR HUMAN-ROBOT COLLABORATION SHARED TASKS - Susanto
The development of technology allows robots to work together with humans with a number of sensors that support aspects of workplace safety. The Industrial Revolution 4.0 also continues to develop by integrating production equipment and computer programs that are connected to the internet network. Technological developments and existing trends trigger the use of robots that work with humans to produce diverse products in small quantities and in a short time. The use of robots that can collaborate with humans has developed both in the automotive industry in Europe and the electronics industry in Indonesia. The use of robots that can collaborate with humans is a way for companies to remain competitive and maintain its existence. The automotive and electronic production process has assembly line to assemble the components into final products that are ready to be sold to consumers. The use of collaboration between humans and robots can also occur in assembly-line. Research that considers the collaboration of humans and robots in assembly is beginning to develop, but there is no specific research for the placement of resources across the assembly-line. This research aims to produce a mathematical model that can help the electronics and automotive industries to place resources in assembly-line consisting of humans and collaborative robots that can work together with humans. The developed mathematical model aims to minimize the cost of production to produce several types of products that can be done by several choices of resources between humans, robots, and collaboration between the two. The purpose of cost minimization is intended so that companies can produce with minimal costs and compete with other companies. The mathematical model created is also intended for companies that want to change their production process from labor-intensive production systems to collaboration between robots and humans for some work that can accelerate the production process of diverse products. Based on experimental results with hypothetical data, it is known that the model functions well and is logically appropriate to solve the problem of the placement of a resource to produce a variety of products that are balanced between workstations in an assembly-line. The novelty of this research is a mathematical model that can choose production resources to do a task that produces the lowest cost between humans, robots, or collaboration to create several types of products in the same assembly line.